EKRANISASI CERITA NOVEL WINTER IN TOKYO ILANA TAN KE FILM WINTER IN TOKYO SUTRADARA FAJAR BUSTOMI - Rahman, Khiratul; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2019)
This study aims to: (a) describe the episode of Ilana Tan's novel Winter In Tokyo; (b) describe the movie episode of Winter In Tokyo by director Fajar Bustomi; (c) describe the episode of Ilana Tan's novel Winter In Tokyonovel with Winter In Tokyo directed by Fajar Bustomi. This research type is qualitative research with descriptive method. This research data is the episode of novelty novel Winter In Tokyo by Ilana Tan and Winter In Tokyo film directed by Fajar Bustomi. Data collection techniques have three stages. First, read Ilana Tan's Winter In Tokyo novel, and then follow Winter In Tokyo directed by Fajar Bustomi. Second, the data collection phase of the novel episode of Winter In Tokyo by Ilana Tan and Winter In Tokyo film by director Fajar Bustomi were collected through recording and observation techniques. Third, the stage of inventorying data into data inventory format. The research findings are episodes of 24 novel episodes, while in the film there are 24 episodes. In the film there are 6 additional episodes, and a reduction of 14 episodes, while the episode of a novel story that changes varies after being turned into a movie, found 7 episodes. It happens because of the creativity of the director while adapting the novel to the movie.Keywords: novel, movie, ekranisasi, episode